Antibiotics in Older Adults - Rodríguez-Julbe, María C.; Ramírez-Ronda, Carlos H.; Arroyo, Elba; Maldonado, Gisela; Saavedra, Sonia; Meléndez, Bebelín; González, Glenda; Figueroa, Javier (Puerto Rico Health Sciences Journal, 2004)
Antibiotics are frequently prescribed in the older person, the dosification needs special care, since the pharmacokinetic parameters changes with aging and the side effects can be different in the older person. The creatinine clearance changes and we must modify the way we prescribe such antibiotics to the elderly, calculating. The variety of antibiotics now available led us to consider this paper in which we have presented the antimicrobial agents that can be considered in the treatment of the older person. We present several groups: the penicillins, cephalosporins, monobactams, carbapenems and betalactamase inhibitors or the great betalactam group. Other trimetroprin-sulfamethoxazole, the newer macrolides (azithromycin and clarithromycin) as well as the aminoglycosides, vancomycin, clindamycin, metroridazole. The indications and contraindications are presented and reviewed.